The Role of Salts and Brønsted Acids in Lewis Acid‐Catalyzed Aqueous‐Phase Glucose Dehydration to 5‐Hydroxymethylfurfural. Issue 3 (17th December 2014) - Wrigstedt, Pauli; Keskiväli, Juha; Leskelä, Markku; Repo, Timo
Abstract The effect of salts and Brønsted acids on the Lewis acid (CrCl3⋅6 H2O)‐catalyzed glucose dehydration to 5‐hydroxymethylfurfural (HMF) in aqueous media are described. We show that the reaction with bromide salts in place of chlorides leads to higher HMF yields. The influence of salts can be attributed to the anions in solution, specifically to the bromide anions enhancing the fructose dehydration step. Additionally, we demonstrate that the reaction kinetics are governed strongly by acidity. Although the fructose dehydration step is accelerated by the addition of Brønsted acids, even on a catalytic scale, a significant retardation of the glucose conversion rate results in a substantial drop in HMF yields. The suppression in glucose‐to‐fructose isomerization rate with increasing acidity is ascribed to the restrained formation of the chromium–glucose chelate complex during the reaction.